Analisis Layanan Tata Kelola Aplikasi Sistem Informasi Akademik dengan Menggunakan Cobit 5 pada STIK Bina Husada - Evariani; Tata Sutabri (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 2023)
Analyze the level of capability in the process of implementing information technology governance that runs at STIK Bina Husada according to national standards. The Academic Information System aims to improve the quality of academic services at the Bina Husada College of Health Sciences, including facilitating the management of student academic data such as student data, student grades/grade transcripts, lecturer data, Study Plan Cards (KRS), and Study Results Cards (KHS). . This is the reason that STIK Bina Husada must regularly carry out the process of monitoring, managing and evaluating the level of readiness of IT services. Based on this, Application Evaluation and Auditcarried out using the Cobit 5 framework, while on Quality Testing and Measurementwebsite using the Apache Jmeter tool. The Cobit 5 processes used are: Risk Optimization (EDM03), Security Management (APO13), Risk Management (APO12), Change Management (BAI06), Operations Management (DSS01), Service Requests (DSS02), Problem Handling (DSS03), Service Security (DSS05), Monitoring and Evaluation of Work (MEA01), Internal Control of Monitoring and Evaluation (MEA02). Gap analysis and Maturity Level are intended to obtain Audit results with good maturity. The results obtained from the average value based on the Gap Analysis of 10 Cobit 5 Processes are 1.2 and the Apache Jmeter test showsthroughput of 101,746/minute and the deviation is 3,671.